A qualitative study of the impact of Crohn's disease from a patient's perspective. Issue 1 (12th May 2016) - Wilburn, Jeanette; Twiss, James; Kemp, Karen; McKenna, Stephen P
Abstract : Objective: To understand how the lives of people with Crohn's disease (CD) are affected. Most research in CD has focused on symptoms and functioning rather than on how these outcomes influence quality of life (QoL). Design: As part of a study to develop a CD-specific patient-reported outcome measure, qualitative interviews were conducted with patients from Manchester Royal Infirmary to determine how CD affects QoL. The needs-based model was adopted for the study. The interviews, which took the form of focused conversations covering all aspects of the impact of CD and its treatment, were audio-recorded. Theoretical thematic analysis of the transcripts identified needs affected by CD. Results: Thirty patients (60% female) aged 25–68 years were interviewed. Participants had experienced CD for between 2 and 40 years. Nearly 1300 statements relating to the impact of CD were identified. Thirteen main need themes were identified: nutrition, hygiene, continence, freedom from infection, security, self-esteem, role, attractiveness, relationships, intimacy, clear-mindedness, pleasure and autonomy. Conclusions: The findings from the interviews indicate that CD has a major impact on need-fulfilment. Such issues should be addressed in CD audit, clinical trials and when evaluating clinical practice.